Survey maps for design purposes in Poland – Technical and legal aspects with particular emphasis on the role of cadastral parcel boundaries - Karabin Marcin (Reports on Geodesy and Geoinformatics, 2025)
The survey map for design purposes is one of the most important cartographic products prepared by licensed surveyors, used to prepare land development projects, which are the basis for obtaining a building permit for a building and other construction objects. One of the most important elements of a map for design purposes are the boundaries of cadastral parcels. They are a determinant for designing the location of objects, because technical regulations specify the minimum distances of various designed objects in relation to the boundaries of cadastral parcels. The stability of geometric data regarding parcels boundaries is therefore crucial in the entire design process, but also in the later stages after the object (building) has been accepted for use by the construction supervision authorities. This stability should be ensured by appropriate geodetic and legal regulations that guarantee the immutability of boundaries (real-time GNSS satellite measurements do not constitute a barrier). This article will present the principles of creating maps for design purposes in Poland but also in another country – in Austria. Reason to take up the subject of comparing Polish solutions with Austrian ones is the existence of the so-called Legal Boundary Cadastre in Austria, which ensures the “stability and immutability” of cadastral parcels boundaries. In the end result, a comparison of the rules of making maps for design purposes will provide guidance as to the recommendation of changes in this area in Poland.